Intertextuality in Ethiopian Gǝ’ǝz Literature: The Lexical Relationships between the Hagiography and the Chronicle of King Iyasu I - Menda, Yonas Yilma (Journal for semitics, 2022)
This paper demonstrates the intertextual aspects of the hagiography and chronicle of an Ethiopian king, aṣe Iyasu I (r.1682-1706). To achieve this, lexical features of both texts are examined. These texts were written in the late seventeenth century. The chronicle of aṣe Iyasu I was written during the king’s reign by his own three chroniclers (Hawarya Krəstos, Zäwäldä Maryam, and Sinoda), while the hagiography of aṣe Iyasu I was written two years after the king’s death by azaž Sinoda. This study is based on textual methods of analysis, in particular content analysis. This method makes it possible to distinguish the lexical relationships between the two texts. For this purpose, the words and phrases that describe the royal courage and sacred personality of the king are identified. Although both the hagiography and the chronicle of aṣe Iyasu I are composed to the same king and address the subject of the same historical milieu, there is no remarkable lexical parallel between the two texts in the area of words and phrases. Unlike the chronicle of aṣe Iyasu I, the hagiography of aṣe Iyasu I uses carefully selected metaphoric words and phrases to describe the king’s bravery and sacred personality. It is thus reasonable to conclude that each author composed their text in a different literary setting rather than that one influenced the other. In other words, the two texts are interconnected but each developed its own textual features as a response to the method and approach of Ethiopian Gǝʿǝz literature.